2008
DOI: 10.1111/j.1467-9280.2008.02211.x
|View full text |Cite
|
Sign up to set email alerts
|

Limits on Introspection

Abstract: Which cognitive processes are accessible to conscious report? To study the limits of conscious reportability, we designed a novel method of quantified introspection, in which subjects were asked, after each trial of a standard cognitive task, to estimate the time spent completing the task. We then applied classical mental-chronometry techniques, such as the additive-factors method, to analyze these introspective estimates of response time. We demonstrate that introspective response time can be a sensitive meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
53
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 36 publications
(48 reference statements)
10
53
2
Order By: Relevance
“…However, even at long SOA the PSE was substantially larger than RT2 (i.e., participants overestimated RT2 by 335 ms). This finding contrasts with previous introspective PRP studies that reported IRT2 being generally smaller than RT2 Corallo et al, 2008;Marti et al, 2010; but see , for slight deviations from this pattern) and suggests that participants cannot accurately estimate their RT2 even when the two tasks are temporally separated and thus do not compete for access to central resources.…”
Section: Resultscontrasting
confidence: 56%
See 4 more Smart Citations
“…However, even at long SOA the PSE was substantially larger than RT2 (i.e., participants overestimated RT2 by 335 ms). This finding contrasts with previous introspective PRP studies that reported IRT2 being generally smaller than RT2 Corallo et al, 2008;Marti et al, 2010; but see , for slight deviations from this pattern) and suggests that participants cannot accurately estimate their RT2 even when the two tasks are temporally separated and thus do not compete for access to central resources.…”
Section: Resultscontrasting
confidence: 56%
“…That is, in the PRP task the conscious perception of S2 is disrupted by the central processing of Task 1 (Corallo et al, 2008;Marti et al, 2010). This explanation implies that timing is relatively intact under dual-task conditions and that the unawareness of the PRP effect occurs because only the conscious parts of Task 2 processing can be timed (see Marti et al, 2010).…”
mentioning
confidence: 99%
See 3 more Smart Citations